A Note on the Measurement of Technical Bias in the U.S. Economy - Zind, Richard G. (The Review of Economics and Statistics, 1979)
1970s (Laidler, 1977, p. 134). If this lack of difference is due to the omission of a risk variable then, since our results indicate a bias toward zero in the estimated partial elasticity for a 1970s-like case, the current demand for money may be more interest elastic than it appears and also it may be more elastic than in the 1930s. The policy implication of a greater interest elasticity in the demand for money is that a given increase in the money supply has less impact upon income.